The ensemble builder - Contemporary Arts Media (Australia : Contemporary Arts Media, 2006)
Featuring award-winning drama teacher Stephe Pritchard and psychologist Ian Frampton, this program shows how to overcome inhibitions and create an environment of intimacy, trust, and communication in an educational setting. It presents ideas, games, and techniques that engage, build confidence, and improve communication among students. The DVD includes examples of work from such theater groups as Goat Island, Forced Entertainment, and Stan Won't Dance. Part 2 CD-ROM contains workshop leaders' notes in HTML format.
DVD format
Keywords: Theater; Movement (Acting); Acting